The pedagogical precariat. Migrants in Ciudad Juárez, Chihuahua - Martinez Montoya, Hugo (2022)
Pedagogical precariat refers to individuals which are socially connected by a scheme of job insecurity. These are individuals working in precarious conditions, school dropouts that suffer from an institutionalized and interiorized cultural capital, and who have also migrated from their place of origin. This study was conducted in the shelter “Casa del Migrante en Juárez”, in Ciudad Juárez (Chihuahua), where 160 forced migrant residents were interviewed between March 7th, 2019 and March 12th, 2020. To identify the pedagocial precariat it was essential to address it from Guy Standing’s definition as a new social class, and from Pierre Bourdieu’s contributions on cultural and economic capital.